Travelling through time. Dialogues among artworks - Jové Monclús, Gloria; Olivera Tabeni, Olga (Pulso. Revista de educación, 2011)
This paper is contextualized in teacher training and it is the result of the analysis of students» works after two visits to the museums of the city of Lleida: an exhibition of contemporary art at Sorigué Foundation and another exhibition at the Museum of Lleida that includes the heritage collections. The students should make a comparison between the two visits. They lived two completely different experiences. The results showed an emerging dichotomous thinking in terms of classical art / contemporary art. We present how can we deconstruct and break this thought in the order to define new proposals to include the dialogues and «travels through time» in the education, in the training and in life.
Keywords: Teacher training; Learning through art; contemporary art; classical art; dichotomous thinking